A Neuro-Metabolic Syndrome that Needs to Be Discovered: A Child with Late Onset Asparagine Synthetase Deficiency - Di Stasio, Fabiana; Faraguna, Martha Caterina; Di Marco, Santo; Crescitelli, Viola; Iascone, Maria; Florio, Santa; Peruzzi, Cinzia; Gasperini, Serena (Journal of Pediatric Epilepsy, 2021)
Asparagine synthetase (ASNS) deficiency is a rare inborn error of metabolism caused by a defect in ASNS—a gene encoding asparagine synthetase. It has mainly been described as a neurological phenotype manifesting as severe developmental delay, congenital microcephaly, spasticity, and refractory seizures; it is not associated with any specific dysmorphisms. ASNS deficiency leads to the inability to synthesize a nonessential amino acid in the brain, this explains why the symptoms are primarily neurological. The accumulation of aspartate/glutamate causes increased neuronal apoptosis leading to brain atrophy and increased neuronal excitability leading to seizures. Asparagine levels in plasma and cerebrospinal fluid are not reliable biomarkers for this disorder, therefore diagnosis is mainly obtained by molecular genetics. This disorder is associated with a poor prognosis and there is no treatment except supportive therapy. Prenatal diagnosis is possible. We report a case of a later onset form, c.146G > A (p.Arg49Gln) variant in the ASNS gene detected by molecular analysis using next-generation sequencing; the patient's clinical presentation included microcephaly, regression of developmental milestones, epilepsy, and hyperthermia.
Keywords: asparagine synthetase deficiency; microcephaly; epilepsy; developmental delay